Enhancing Access and Inclusion: The Retrofitting of Olympic Facilities for the Paralympic Games - Lawrence W Judge; Jeffrey Petersen; Adam Smith; Kyra Livergood (Journal of Applied Sports Management, 2024)
This critical review examines the strategies and challenges in adapting Olympic facilities for Paralympic use. A synthesis of recent literature evaluates successful retrofitting initiatives, elucidates ongoing challenges, and assesses the repercussions of global events on the dynamic process of facility conversion. The resulting analysis culminates in evidence-based recommendations for future investigations and the operational enhancement of Paralympic venues. These findings suggest that adopting a collaborative approach, anchored in universal design principles and preemptive planning, is imperative to developing accessible, efficient, and ecologically responsible Paralympic infrastructures.
Keywords: accessibility; inclusivity; equality; equity; retrofitting